2012
DOI: 10.4028/www.scientific.net/kem.510-511.467
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Post-Deposition Annealing Treatment on the Structural, Optical and Gas Sensing Properties of TiO<sub>2</sub> Thin Films

Abstract: One of the potential applications of TiO2 is its use in gas sensor technology. The aim of this work was to study the gas sensing properties of TiO2 thin films in combination with the effect of post-deposition annealing treatment. Titanium dioxide thin films with thickness 100 nm were prepared by the reactive dc magnetron sputtering. The thin films were deposited on sapphire substrate from a titanium target in an oxygen atmosphere. The samples were then post-annealed in air in the temperature range 600 °C 1000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…This potential barrier arises due to trapping of electrons by pre-adsorbed oxygen and subsequently developing a depletion region on the surface [35,36]. This is noticeable in our measurement that Cr-doped TiO 2 NTs showed higher values of resistance R=≈800 MΩ than R=≈5 kΩ of un-doped TiO 2 NTs at 500 °C.…”
Section: Operating Temperature Dependent Resistancementioning
confidence: 64%
“…This potential barrier arises due to trapping of electrons by pre-adsorbed oxygen and subsequently developing a depletion region on the surface [35,36]. This is noticeable in our measurement that Cr-doped TiO 2 NTs showed higher values of resistance R=≈800 MΩ than R=≈5 kΩ of un-doped TiO 2 NTs at 500 °C.…”
Section: Operating Temperature Dependent Resistancementioning
confidence: 64%
“…(2), causes some release of the captured electrons back to the metal-oxide surface resulting in a decrease of the upward band bending and ultimately a decrease in the resistance (Batzill, 2006;Haidry et al, 2012b). This is valid also for reducing gases (see e.g., Fig.…”
Section: Humidity Sensing Mechanismmentioning
confidence: 68%
“…In our previous works [2,3], we have reported that the annealing temperature at which the phase transitionfrom Anatase to Rutile for TiO 2 thin films prepared in our laboratory by dc magnetron sputtering methodtook place was 700 °C -800 °C. In this work we limited our research to only anatase thin films annealed up to 800 °C.…”
Section: Resultsmentioning
confidence: 98%
“…In the present work, TiO 2 thin films were prepared by reactive dc magnetron sputtering method from Ti target [2,3]. The thickness of the thin films was determined from SEM image in cross-section to be 100 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation